1996
DOI: 10.1073/pnas.93.13.6621
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the two cytosolic domains of mammalian adenylyl cyclase.

Abstract: Adenylyl cyclase activity can be reconstituted by simple mixture of the two cytosolic domains of the enzyme after their independent synthesis in Escherichia coli. We have synthesized and purified the Cla domain of type I adenylyl cyclase and the C2 domain of the type II enzyme to assess their interactions with each other and with the activators Gs,, and forskolin. In the absence of an activator, the fragments associate with low affinity and display low catalytic activity.This basal activity can be stimulated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
118
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 10 publications
8
118
0
Order By: Relevance
“…The fact that the G s␣ binding site that we have determined by the mutational analysis comprises residues located in both C 1 and C 2 domains is consistent with the observation that G s␣ increases the affinity of the cytoplasmic domains for each other (37,38). That most of the G s␣ -insensitive mutants isolated in this study map to residues in the C 2 domain is consistent with the observation that recombinant soluble C 2 domain constructs can bind to G s␣ in vitro, whereas the C 1 domain cannot but can be covalently attached to G s␣ in the presence of chemical crosslinkers (39).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The fact that the G s␣ binding site that we have determined by the mutational analysis comprises residues located in both C 1 and C 2 domains is consistent with the observation that G s␣ increases the affinity of the cytoplasmic domains for each other (37,38). That most of the G s␣ -insensitive mutants isolated in this study map to residues in the C 2 domain is consistent with the observation that recombinant soluble C 2 domain constructs can bind to G s␣ in vitro, whereas the C 1 domain cannot but can be covalently attached to G s␣ in the presence of chemical crosslinkers (39).…”
Section: Discussionsupporting
confidence: 88%
“…Mutation of this aspartate would disrupt its ability to hydrogen-bond to the backbone nitrogen of these residues, thereby decreasing the interaction of the two cytoplasmic domains. In light of the finding that both G s␣ and forskolin activate adenylyl cyclase by increasing the affinity of C 1 for C 2 (37,38), the predicted consequence of mutating Asp-424 would be precisely what was observed for the D424N mutant: reduced sensitivity to stimulation by either forskolin or G s␣ alone, and a retention of the ability to synergistically integrate these stimulatory inputs.…”
Section: Discussionmentioning
confidence: 90%
“…1A). Recent studies from Gilman and coworkers have demonstrated that AC activity can be reconstituted by the expression of the two major cytosolic regions of type I and II enzyme that are either joined together by a linker (20) or expressed separately and then mixed together (21). Thus, the engineered soluble forms of AC not containing the membrane spanning regions can be utilized to investigate the regions on the molecule that are important for its regulation by various modulators.…”
mentioning
confidence: 99%
“…BW245C at 10 μM induced about 6-fold increase, while 300 nM forskolin induced about 11-fold increase in intracellular cAMP level. Forskolin is known to bind directly to the catalytic subunit of AC, therefore leading to abundant cAMP increase (26).…”
Section: Discussionmentioning
confidence: 99%